In vitro evaluation of antidermatophytic activity of five lichens. Issue 1 (31st December 2016) - Pathak, Ashutosh; Mishra, Rohit K.; Kant Shukla, Shashi; Kumar, Rajesh; Pandey, Madhu; Pandey, Manisha; Qidwai, Afifa; Dikshit, Anupam
Abstract: Lichens (a composite organism) are known for their secondary metabolites and have several properties as photoprotection, allelopathy, antioxidant, antimicrobial, and antiviral. In this study, based on alarming situation of prevalence and developing resistance in dermatophytes, the new biological source in the form of lichens was screened for their antidermatophytic potential. Three dermatophytes viz. Microsporum canis, Trichophyton mentagrophytes, and Trichophyton rubrum were procured from Microbial Type Cell Culture, Chandigarh, India and susceptibility of aforementioned pathogens were tested via Clinical Laboratory and Standard Institute recommended broth microdilution procedure for filamentous fungi. Five lichens viz. Bulbothrix setschwanensis, Myelochroa aurulenta, Parmotrema nilgherrense, Parmotrema reticulatum, and Ramalina conduplicans were tested for their antidermatophytic activity (fungistatic and fungicidal concentrations) in the form of MIC and MFC values. M. aurulenta exhibited most promising MIC and MFC values against all dermatophytes and provides new leads in the form of secalonic acid A and leucotylic acid for future investigations.